Intensivists' perceptions of unconsented HIV testing in South African academic intensive care units (ICUs) - Singh, Dhivendra (My University, 2016)
Introduction The National Health Act of 2003 and guidelines from the Health Professions Council of South Africa (HPCSA) and the South African Medical Association (SAMA) require consent for Human Immunodeficiency Virus (HIV) testing. However, critically ill patients in the intensive care unit (ICU) are often unable to provide informed consent. Currently there is little guidance for South African intensivists when HIV testing is necessary and informed consent cannot be obtained. Aims To ascertain the views of intensivists with respect to unconsented HIV testing of patients in South African ICUs and to investigate the factors that influence their current practice in that regard. Objectives The objectives of the study were (1) to determine the availability of protocols to guide unconsented HIV testing in different South African ICUs; (2) to assess the views of South African intensivists on (i) the importance of HIV testing in their ICU; (ii) the ethics of unconsented HIV testing; (3) to describe the current practice of intensivists when they consider HIV testing is necessary, but are unable to obtain informed consent from the patient; and (4) to provide some practical recommendations with regard to HIV testing in the ICU. Methods The study was a descriptive, cross-sectional survey of academic hospital staff intensivists. Results The response rate was 51% and most respondents had more than 5 years of experience in critical care. The majority (79%) did not have protocols or policies for HIV testing in their ICUs. Unconsented HIV testing was considered to be ethical by 83% of respondents and 87% were comfortable with ordering HIV tests in critically ill patients. Opinions were relatively evenly split in terms of wanting to know the HIV status of all patients. Most respondents considered current guidelines inadequate and felt that they were not in the best interests of the patient. The majority did not believe that surrogate consent was either reliable or acceptable and felt that HIV testing should be at the discretion of the physician. If the patient recovered, most respondents felt that the results should not be available to the family or spouse, but should be available to the patient. If the patient demised, most respondents agreed that the result should be recorded on the death certificate and made available to the spouse or partner, but not be available to the patient’s family. Conclusion Intensivists may view testing for HIV without consent in selected cases as ethical and in the patient’s best interest when it may guide diagnosis and therapy, but most ICUs do not have established policies and protocols to guide such HIV testing. A way forward would be for ICU directors to develop ethical protocols for HIV testing in the ICU. HIV positive patients are socially vulnerable and it may be difficult to establish protocols for HIV testing without consent.
A research report submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Medicine (Bioethics & Health Law), Steve Biko Centre for Bioethics. Johannesburg 2016